MSME Empowerment Strategy: A Literature Review - Titin Dunggio; Abjul Basri (West Science Journal Economic and Entrepreneurship, 2023)
By creating jobs and improving people's welfare, micro, small and medium enterprises (MSMEs) play a significant role in economic development. Limited capital, lack of innovation, traditional marketing, inefficient financial management, poor branding, and lack of utilization of online marketing due to not understanding technology are some of the challenges often faced by MSMEs. The purpose of this study is to help small and medium enterprises (MSMEs) compete in the market. This study used literature research. In this situation, an aggressive growth-oriented strategy is suggested. Combining digital marketing elements such as content marketing, blogs, search engine optimization (SEO), social media marketing, and branding with community empowerment through training, demonstrations, and mentoring is one relevant alternative strategy.